Globalização, Neoliberalismo e lutas de classes no Brasil (1990-2010) - Barbosa, Túlio (2015)
This work was aimed at the history of the present in a marxist construction highlighting globalization as an ongoing process since the first expansion of the capitalist market and neo-liberalism as a step in this process which has focused the expansion of the financial market and also expansion of transnational and multinational companies that hold considerable power over the peripheral countries of the system. We think Brazil in this process the decades of 1990-2010 by economic and political issues that have contributed significantly to the country to be inserted into the neoliberal economic policies. Construction work is the centrality of class struggle as a necessary condition to understand the contradictions of capitalism at the same time that help reflect the conditions of the working class.